2007
DOI: 10.1143/jjap.46.3981
|View full text |Cite
|
Sign up to set email alerts
|

Approach of Improving Disk Performance to High-Quality Gap Control in Near-Field Optical Disk Drive System

Abstract: A computer-aided method is developed for automatically correcting the slide distortions of torque curves measured with a non-zero torque magnetometer. This method is based on a previously obtained analytic expression of the first harmonic corresponding to the distorted calibration torque curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…With respect to the disk, we proposed a disk with high damping characteristics instead of a conventional polycarbonate substrate. 7) As the spindle motor for the NFDD system, we developed a high-precision motor with vertical and radial run-out less than 1 mm. 5) We have also improved the mechanical performance of the SIL actuator as the servo objective.…”
Section: Servo Technologies For the Nano-gapmentioning
confidence: 99%
“…With respect to the disk, we proposed a disk with high damping characteristics instead of a conventional polycarbonate substrate. 7) As the spindle motor for the NFDD system, we developed a high-precision motor with vertical and radial run-out less than 1 mm. 5) We have also improved the mechanical performance of the SIL actuator as the servo objective.…”
Section: Servo Technologies For the Nano-gapmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] It can exhibit a large capacity and a highdata transfer rate towards recording next-generation ultrahigh-definition television [i.e., Super Hi-Vision (SHV), 7320 Â 4320 pixels] video signals 17,18) for home-use. Fourfold higher density recording using NFR optical disks with 1.2-mm-thick disks has been reported, 12,14) and studies of larger capacity using multilayer recording using NFR have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A near-field optical recording (NFR) system using a solid immersion lens (SIL) 1) has a fourfold higher recording density than the Blu-ray disc system. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Some studies have shown the realization of a large recording capacity using multilayer recording techniques for optical disks, [17][18][19][20][21] but the data transfer rate is limited. The NFR system is expected to realize not only a large capacity but also a high data transfer rate because its numerical aperture (NA) is more than two times higher and the optical beam spot can be less than half the diameter of current Blu-ray optical systems.…”
Section: Introductionmentioning
confidence: 99%